Exploring an ESL teachers' beliefs and practices of teaching literary texts: A case study in Hong Kong. (January 2023) - Cheung, Anisa; Hennebry-Leung, Mairin
Although much has been written about the relationship between teachers' beliefs and practices, research examining the role of emotions in the realm of teacher cognition remains limited. This article presents a case study investigating one English as a second language (ESL) teacher's beliefs and practices about teaching literary texts, drawing on Zembylas' three levels of teacher emotions (2002, 2005), i.e. intrapersonal, interpersonal and intergroup, as the conceptual framework. The ESL teacher's beliefs and practices were investigated via open-ended interviews and lesson observations that explored her perceptions of teaching literary texts throughout one academic year. The findings point to the complexity of teacher practices which may converge or diverge with their beliefs. Various contextual factors were found to contribute to this complexity. The results highlight the need to situate the emotions of teachers beyond contextual factors and consider the dynamic nature of teacher cognition. The practical value of the study lies in its extension of the role of emotions in mediating teacher cognition.